Southern Ocean Precipitation and Aerosol-Cloud-Precipitation Interactions: A Synthesis of Aircraft Observations, Simple Process Model, and Earth System Model - Kang, Litai (My University, 2024)
The Southern Ocean (SO) plays a crucial role in the climate system with ubiquitous low clouds and a preindustrial-like pristine environment. However, accurately representing its aerosols, clouds, and precipitation remains challenging for climate models. Moreover, the properties of SO aerosols and precipitation are not currently well-constrained by satellite observations. The overarching objective of this dissertation is to characterize precipitation from the SO summertime stratocumulus using aircraft observations collected during the Southern Ocean Clouds Radiation Aerosol Transport Experimental Study (SOCRATES), and study sources and sinks of SO aerosols using both a simple theoretical budget model and simulations from the Energy Exascale Earth System Model (E3SM) run at high-resolution for a climate model, about 3 km. In Chapter 2, data from airborne radar, lidar, and in situ probes are used to derive liquid precipitation properties based on a hierarchy of retrieval methods from simple Z-R relationships to more complex radar reflectivity-velocity and radar-lidar retrievals. The retrieved rain rate from all three methods shows good agreement with in-situ aircraft estimates, with rain rates typically being quite light (<0.1 mm hr-1). The derived data are further used to study the vertical distribution of a variety of precipitation properties and to examine the dependence of rain rate on cloud depth and aerosol concentration. In Chapter 3, a simple source-and-sink budget model for cloud droplet number (Nd) is constrained by aircraft observations and is used to examine the relative influence of processes that determine Nd in SO stratocumulus clouds. The model predicts Nd with little bias and a correlation coefficient of ~0.7 compared with observations. Coalescence scavenging is found to be an important sink of CCN in precipitating stratocumulus and reduces the predicted Nd by as much as 90% depending on the precipitation rate. I also find that the free tropospheric aerosol controls Nd more strongly than the surface aerosol source during the austral summer. In Chapter 4, a diverse set of simulations and observations are used to evaluate and untangle biases in E3SMv2 simulated clouds, aerosols, and sulfur aerosol species. The default E3SMv2 underestimates cloud droplet numbers and aerosol concentration when compared with observations. Updating the DMS emission and chemistry improves agreement between the model and the observations in cloud droplet numbers and boundary layer aerosols, though biases remain in the free troposphere aerosols, likely attributable to insufficient particle growth, and in simulated sulfur species, due to incomplete DMS chemistry.
Thesis (Ph.D.)--University of Washington, 2024
Keywords: aerosols; aircraft; clouds; precipitation; radar; southern ocean; Atmospheric sciences; Atmospheric sciences